Two weeks as a chemist - Zambrotta, Maria; Mazzuia, Daniela (Open Schools Journal for Open Science, 2019)
“Two weeks as a chemist” is a project developed for sixteen-year-old students from the Secondary School Santorre di Santarosa (Turin). The project aims to increase students’ motivation and interest in science by providing them a working experience in a chemist’s store and is made with the collaboration between schools and local stakeholders. It encourages the use of new methodologies in the classroom and the contextualization of STEM learning.